From the Secretary’s Desk to Main Street: Change and Transition in the British Columbia Credit Union Movement, 1936‑1960 - MacPherson, Ian (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1987)
AbstractFrom its founding in 1936 to roughly 1960, the credit union movement in British Columbia focused on the financial emancipation of lower-income British Columbians. As such it was one of a number of similarly inspired institutions, which included adult education centres, cooperatives, trade unions and the CCF.In spite of the existence of Canadian prototypes — the caisse populaire movement in Quebec and, what inspired the BC credit unions in the first place, the Antigonish movement in Nova Scotia — the BC experience generally followed the American model. The first experiments in cooperatives date to the 1860s, but early efforts were sporadic and uncoordinated. Started initially in 1932 by Vancouver's Army of the Good and encouraged by, among several organizations, the CCF, credit unions were given legal standing late in 1939. Once authorized, these institutions expanded rapidly; 139 were established before the end of the war. They answered a felt need to promote savings and encourage the responsible handling of cheaper levels of credit.By 1960, however, the British Columbian credit union movement was reaching the end of its emancipatory stage and had drifted far from its roots. Initially founded on the economic populism of the Antigonish movement, it absorbed many of the organizational techniques and some of the conservatism which characterized the American movement.